Assessing small-scale youth fishermen adaptation ability towards climate change - Saharrudin, Nurul Farhana; Abu Samah, Asnarulkhadi; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2018)
This study aims to assess the adaptation ability towards climate change among youth small-scale fishermen. This study is quantitative in nature whereby via a multistage cluster sampling, a total of 203 respondents from four fisheries districts had been selected. The resulted analysis confirmed small-scale youth fishermen strong attachment to place and area, strong environmental awareness, values and attitudes, and strong formal and informal networks. The resulted analysis also confirmed their weakness to adapt in relation to employability, business size, and approach and livelihood diversity. Several recommendations are made for concerned agencies, which are to focus on exposing small-scale youth fishermen towards advanced fisheries technologies, to provide entrepreneurship opportunities, to advise them on good financial planning and management, and financial assistance.